Can BioSAXS detect ultrastructural changes of antifungal compounds in Candida albicans?–an exploratory study - Hilpert, Kai; Rumancev, Christoph; Gani, Jurnorain; Collis, Dominic W. P.; Lopez-Perez, Paula Matilde; Garamus, Vasil M.; Mikut, Ralf; Rosenhahn, Axel (Frontiers in Pharmacology, 2023)
The opportunistic yeast Candida albicans is the most common cause of candidiasis. With only four classes of antifungal drugs, resistance is becoming a problem in the treatment of fungal infections, especially for in immunocompromised patients. The development of novel antifungal drugs with different modes of action is urgent. In 2016, we have developed a groundbreaking new medium-throughput method to distinguish the effects of antibacterial agents. Using small-angle X-ray scattering for biological samples (BioSAXS) it is now possible to screen hundreds of new antibacterial compounds and select those with the highest probability for a novel mode of action. In the pioneering work described here, we explored the possibility to expand this method towards eukaryotic cells. For this exploratory study, we used the yeast Candida albicans and treated it for 40 minutes with a known antifungal drug (Flucocytosin) and five antifungal peptides (1. Cecropin A - melittin hybrid [CA(1-7)M(2-9)], KWKLFKKIGAVLKVL; 2. Lasioglossin LL-III, VNWKKILGKIIKVVK; 3. Mastoparan M, INLKAIAALAKKLL; 4. Bmkn2, FIGAIARLLSKIFGKR and 5. optP7, KRRVRWIIW). BioSAXS curves were analysed using a principal component analysis (PCA). The PCA revealed that Flucocytosin has a different mode of action from all five peptides tested. In addition, the modes of action of those peptides differ from each other, except Cecropin A - melittin hybrid [CA(1-7)M(2-9)] and optP7 show very similar effects on Candida albicans. This very first exploratory study demonstrates that BioSAXS shows great promise to be used for antifungal drug development. BioSAXS could therefore accelerate and de-risk antifungal drug development.